2016
DOI: 10.1128/aac.01835-15
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plasmodium vivax Dihydropteroate Synthase Polymorphisms in Sulfa Drug Resistance

Abstract: Dihydropteroate synthase (DHPS) is a known sulfa drug target in malaria treatment, existing as a bifunctional enzyme together with hydroxymethyldihydropterin pyrophosphokinase (HPPK). Polymorphisms in key residues of Plasmodium falciparum DHPS (PfDHPS) have been characterized and linked to sulfa drug resistance in malaria. Genetic sequencing of P. vivax dhps (Pvdhps) from clinical isolates has shown several polymorphisms at the positions equivalent to those in the Pfdhps genes conferring sulfa drug resistance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…A survey of other organisms was conducted to determine which of these mutations is conserved across species (Table 2 ). Mutations equivalent to F17L were found in Neisseria meningitidis and Escherichia coli , and mutations equivalent to T51M were found in Plasmodium species, Pneumocystis carinii, Mycobacterium leprae , and Streptococcus pneumoniae (Dallas et al, 1992 ; Fermer et al, 1995 ; Lane et al, 1997 ; Maskell et al, 1997 ; Wang et al, 1997b ; Elena et al, 1998 ; Kazanjian et al, 1998 ; Mei et al, 1998 ; Kai et al, 1999 ; Williams et al, 2000 ; Pornthanakasem et al, 2016 ). A mutation homologous to E208K was also found in Plasmodium species but not in conjunction with any of the primary mutations (Pornthanakasem et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…A survey of other organisms was conducted to determine which of these mutations is conserved across species (Table 2 ). Mutations equivalent to F17L were found in Neisseria meningitidis and Escherichia coli , and mutations equivalent to T51M were found in Plasmodium species, Pneumocystis carinii, Mycobacterium leprae , and Streptococcus pneumoniae (Dallas et al, 1992 ; Fermer et al, 1995 ; Lane et al, 1997 ; Maskell et al, 1997 ; Wang et al, 1997b ; Elena et al, 1998 ; Kazanjian et al, 1998 ; Mei et al, 1998 ; Kai et al, 1999 ; Williams et al, 2000 ; Pornthanakasem et al, 2016 ). A mutation homologous to E208K was also found in Plasmodium species but not in conjunction with any of the primary mutations (Pornthanakasem et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the double mutant allele ( G 383 G 553 ) displays reduced binding affinity between the PvDHPS domain and sulfadoxine in vitro and in vivo compared to the wild-type allele ( Imwong et al, 2005 ; Barnadas et al, 2011 ). However, it has also been reported that other mutations in the gene, including S382A, A383G and A553G, do not influence enzyme catalytic activity ( Pornthanakasem et al, 2016 ). We did not detect mutations at V585 in any isolates in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 evaluation in Colombia’s Córdoba department [ 17 ] stated that the P. vivax population was more genetically diverse than it had been thought. However, some genome regions had low diversity due to a selective sweep associated with the PvDHPS A383G allele [ 17 ] which, in turn, has been associated with sulfadoxine resistance [ 18 ]. The region surrounding PvDHFR did not have a loss of genetic diversity, as with PvDHPS; nevertheless, two alleles (S58R and S117N) [ 17 ] were reported to be associated with SP resistance [ 11 ].…”
Section: Introductionmentioning
confidence: 99%